One-pot Multicomponent Reaction: An Efficient Synthesis of 4-(Het)Aryl-substituted Pyrazolo-quinolinones - Beker, Hueseyin Kerim; Kaban, Seniz (BENTHAM SCIENCE PUBL LTD, 2024)
Introduction Pyrazolo-quinolinones (PQs) are a versatile class of Organic chemistry and it was found that they have very advanced functionally promising as selective compounds due to their scaffold and demonstrated low toxicity and considerable clinical promise. Moreover, these compounds have an important role in different applications such as analytical reagents, technical, pharmaceutical development, and biological markers. So, we aimed to synthesize and characterize new 4-(Het)aryl-substituted Pyrazole-quinolinones.Methods Synthesis of One-Pot Multicomponent Reaction was carried out with the reaction of 5-amino-3-methyl-1H-pyrazole 1a, and 5-amino-3-phenyl-1H-pyrazole 1b and dimedone 2 with some (het)aryl aldehydes 3 using ethanol. Characterizations such as the linear structures and the regiospecificity of the reactions were determined by using NMR, GC-MS, IR, and UV measurements.Results and Conclusion This research will be very useful for all methods and procedures using multi one-point reactions which are very popular in the synthesis of heterocyclic systems for pyrazole- quinoline skeleton synthesis.
Keywords: Regiospecific pyrazole cyclo-condensation; (het)aryl aldehyde; multicomponent reaction; pyrazolo[3,4-b]quinoline; organic chemistry; heterocyclic compound; Chemistry